Configuration schemes for modeling and simulation as a service federation. (November 2013) - Cayirci, Erdal
Two types of modeling and simulation as service configuration problems are formally defined and their complexities are analyzed. Optimization and heuristic solutions for these configuration problems are introduced. The important engineering parameters related to the schemes and their scalability are also investigated.